Comparison of variant allele frequency and number of mutant molecules as units of measurement for circulating tumor DNA. Issue 1 (31st October 2020) - Bos, Manouk K.; Nasserinejad, Kazem; Jansen, Maurice P. H. M.; Angus, Lindsay; Atmodimedjo, Peggy N.; de Jonge, Evert; Dinjens, Winand N. M.; van Schaik, Ron H. N.; Del Re, Marzia; Dubbink, Hendrikus J.; Sleijfer, Stefan; Martens, John W. M.
Abstract : Quantification of tumor‐specific variants (TSVs) in cell‐free DNA is rapidly evolving as a prognostic and predictive tool in patients with cancer. Currently, both variant allele frequency (VAF) and number of mutant molecules per mL plasma are used as units of measurement to report those TSVs. However, it is unknown to what extent both units of measurement agree and what are the factors underlying an existing disagreement. To study the agreement between VAF and mutant molecules in current clinical studies, we analyzed 1116 TSVs from 338 patients identified with next‐generation sequencing (NGS) or digital droplet PCR (ddPCR). On different study cohorts, a Deming regression analysis was performed and its 95% prediction interval was used as surrogate for the limits of agreement between VAF and number of mutant molecules per mL and to identify outliers. VAF and number of mutant molecules per mL plasma yielded greater agreement when using ddPCR than NGS. In case of discordance between VAF and number of mutant molecules per mL, insufficient molecular coverage in NGS and high cell‐free DNA concentration were the main responsible factors. We propose several optimization steps needed to bring monitoring of TSVs in cell‐free DNA to its full potential. Abstract : Here, we compare the number of mutant molecules and the variant allele frequency as units of measurement for circulating tumor DNA. We conclude that when using digital droplet PCR, both units of measurement yield greater agreement than when using next generation sequencing. Low frequent mutations and molecular coverage are important factors affecting agreement. These results will improve circulating tumor DNA analysis, contributing to better cancer patient management.